2017
DOI: 10.1039/c6ra28801d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cell uptake and antitumor activity of selenadiazole derivatives through interaction and delivery by serum albumin

Abstract: A series of selenadiazole derivatives has been synthesized and exhibit potent anticancer efficacy through interaction and delivery by serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The majority of examples have the selenadiazole molecules disposed about a centre of inversion. In four examples, that is 16 [73], 19 [73], 23 [69] and 35 [77], two independent molecules comprise the crystallographic asymmetric-unit and these are connected into a supramolecular dimer. There is a single example, that is 12 [69], where there are two independent molecules and each of these selfassociates about a centre of inversion.…”
Section: Two-molecule Aggregates Featuring Two Se … N Interactions: Selenadiazole Ringsmentioning
confidence: 99%
“…The majority of examples have the selenadiazole molecules disposed about a centre of inversion. In four examples, that is 16 [73], 19 [73], 23 [69] and 35 [77], two independent molecules comprise the crystallographic asymmetric-unit and these are connected into a supramolecular dimer. There is a single example, that is 12 [69], where there are two independent molecules and each of these selfassociates about a centre of inversion.…”
Section: Two-molecule Aggregates Featuring Two Se … N Interactions: Selenadiazole Ringsmentioning
confidence: 99%
“…Furthermore, it inhibited U87 tumor (glioblastoma) spheroids growth in vitro and prolonged blood circulation time . Several alkyl benzo­[ c ]­[1,2,5]­selenadiazole-5-carboxylates were prepared and found to have a moderate activity (the lowest IC 50 being 28 μM) in several cancer cell lines . More importantly, it was found that 1,2,5-selenadiazoles bind to bovine serum albumin (BSA) through lipophilic interactions, improving cellular uptake .…”
Section: 25-selenadiazolesmentioning
confidence: 99%
“…Chalcogenides are compounds containing one or more chalcogen elements and have an important role to play in biology and, in particular,i nh uman health and the human body.S elenium, in the form of selenocysteine and the sec unit in the proteins (peptides), plays an important enzymatic antioxidant role in the body.R ecent advances have revealed thath eterocyclic selenium-containing compounds are important for biological activities, such as antibacterial,a nti-inflammatory,a ntitumor,a nd for ROS/RNS sensing. [29][30][31][32][33][34][35][36][37] In this part, we are reviewing recent progress to synthesize chalcogen-based chemosensors and their photophysical underpinnings. This work focuses on small chromophoric or fluorophoricm olecules, which are incorporated with organochalcogen atoms (e.g.,R -S-R, R-Se-R, R-Te-R).…”
Section: Oxidation Of Organochalogen To Their Tetravalent (E = O) Oxidesmentioning
confidence: 99%
“…Selenium, in the form of selenocysteine and the sec unit in the proteins (peptides), plays an important enzymatic antioxidant role in the body. Recent advances have revealed that heterocyclic selenium‐containing compounds are important for biological activities, such as antibacterial, anti‐inflammatory, antitumor, and for ROS/RNS sensing . In this part, we are reviewing recent progress to synthesize chalcogen‐based chemosensors and their photophysical underpinnings.…”
Section: Introductionmentioning
confidence: 99%